21‐2: Free‐Form Incell‐Touch TFT‐LCD Vehicle Displays Based on LTPS. Issue 1 (29th May 2019) - Wu, Wei; Zhou, Xiufeng; Liu, Jian; Chen, Rong; Zou, Zongjun; Deng, Zhuo; He, Qilian; Shen, Boping; Lee, ChunYi
Abstract : In recent years, with the popularity of vehicle display applications and consumers provide higher requirements for vehicle display resolution, appearance. of shape and touch operation. LTPS will be used by more and more OEMs. This research adopts reasonable sensor and architectures design to realize a narrow border, free‐form, incell‐touch vehicle display with LTPS technology.